Toilet Sanitation Management in Supporting the Implementation of Public Services - Novie R. A. Palar; Florence D. J. Lengkong; Femmy M.G. Tulusan; Helly F. Kolondam (Journal La Sociale, 2022)
Good toilet sanitation management will not only provide added value in service satisfaction but is also a reflection of personal and environmental hygiene. However, toilet sanitation is one of the problems that people often complain about when they are in government offices. The availability of good toilet sanitation facilities has not been a concern of the government until now. This research was conducted using a qualitative design, collecting data directly or using google form and making direct observations of the condition of the toilet and its management. Data collection was also carried out using researchgate, google scholars and google scholars. By using systematic literature review technique data analysis and the use of primary data, it was found that the management of toilet sanitation in government offices was not good as seen from the quality of cleanliness and availability of facilities. There is no work unit available and responsible for toilet sanitation hygiene. The government can fix this by collaborating with third parties with a cleaning service workforce outsourcing system.